JCER 2018
DOI: 10.30950/jcer.v14i3.883
|View full text |Cite
|
Sign up to set email alerts
|

The European Union under Threat of a Trend toward National Sovereignty

Abstract: The European Union represents the most advanced case of voluntary regional integration in the world. But today, after several decades of the pooling of sovereignty within the EU, Europe is experiencing a renaissance of national sovereignty supported by a nationalistic turn of public opinion and represented by parties on both ends of the political spectrum. The size of the national sovereignty trend among European citizens and discovery of its main drivers are the main problems that we address in the article. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…in their overall view (see descriptive statistics in Table 2), we found that it is among those particular segments more in favour of state intervention that support for further EU integration should be sought. In our view, this result is quite surprising and goes against previous findings on the positive correlation between liberal values and support for EU integration among the broad population (Conti et al, 2018b). Turning now to the control variables, while different levels of Extremism have little or no effect on business elites' attitudes on EU integration, when business elites are more in favour of redistribution from richer to poorer (Favour Redistribution), all other things being equal, they are more in favour of further EU integration (a positive and statistically significant relationship is documented in all models).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…in their overall view (see descriptive statistics in Table 2), we found that it is among those particular segments more in favour of state intervention that support for further EU integration should be sought. In our view, this result is quite surprising and goes against previous findings on the positive correlation between liberal values and support for EU integration among the broad population (Conti et al, 2018b). Turning now to the control variables, while different levels of Extremism have little or no effect on business elites' attitudes on EU integration, when business elites are more in favour of redistribution from richer to poorer (Favour Redistribution), all other things being equal, they are more in favour of further EU integration (a positive and statistically significant relationship is documented in all models).…”
Section: Discussioncontrasting
confidence: 99%
“…In the presence of business elites who are not necessarily so liberal in their overall view (see descriptive statistics in Table 2), we found that it is among those particular segments more in favour of state intervention that support for further EU integration should be sought. In our view, this result is quite surprising and goes against previous findings on the positive correlation between liberal values and support for EU integration among the broad population (Conti et al ., 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a sovereignist upsurge advocates a return to an international order where states take back control over laws, policy and international interactions and focus on the protection of the self-identified interests of the native population (De Spiegeleire et al 2017). In this perspective, supranational institutions and global market forces have become the main target of a sovereignist course of action, as have immigrants who, in the same perspective, are seen as 'outsiders' to the native population and its interests (Conti et al 2018). If sovereignty refers to the political authority of governing bodies within a bounded territory, sovereignism specifically claims political control within the boundaries of the traditional nation state.…”
Section: The Importance Of Sovereignism For Political Competitionmentioning
confidence: 99%
“…This type of analysis is particularly relevant for the case of Brexit, where numerous authors have emphasised that rather than a simple conflict between the United Kingdom and the EU (Börzel, 2018; Conti and Di Mauro Memoli, 2018), what was observed in debates was also a horizontal conflict of sovereignty about who rules within the United Kingdom (Bickerton, 2019; Bogdanor, 2016; Lord, 2020; Rone, 2021). This claim has been confirmed also in a recent empirical analysis of Brexit’s ‘politics of division’ as explored in online social campaigning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%